1988
DOI: 10.1007/bf01805838
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Ha-RAS-1 proto-oncogene alleles in breast cancer patients and in a control population

Abstract: SummaryThe frequencies of 13 different Ha-ras proto-oncogene alleles have been estimated in 92 breast cancer patients and 60 unaffected individuals. The Ha-ras alleles can be identified using a DNA restriction fragment length polymorphism (RFLP) closely linked to the 3' end of the gene, and are characterized by a different length due to a region of sequences repeated a variable number of times (variable tandem repeats, VTR).The statistica] analysis of the data obtained shows that the frequency of alleles rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The published studies (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) that have examined an association of inheritance of the H-ras-I VTR with breast cancer are remarkably consistent. All find a positive association and most are statistically significant ( Figure 2).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The published studies (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) that have examined an association of inheritance of the H-ras-I VTR with breast cancer are remarkably consistent. All find a positive association and most are statistically significant ( Figure 2).…”
Section: Discussionmentioning
confidence: 91%
“…In intron 3 there is a biallelic 16 bp insertion/deletion (56 (61) reported that individuals who inherited rare alleles were at increased risk of cancer. In the intervening years, numerous investigators have tried to replicate these findings in specific cancer types through case-control studies (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and family studies (32,33), with varying success.…”
Section: Introductionmentioning
confidence: 99%
“…118 The HRAS1 polymorphism was examined in 13 studies. [119][120][121][122][123][124][125][126][127][128][129][130][131] Positive ORs were detected in all studies (fig 1), five of which reached significance 119 124 128 129 131 with ORs of 2-7. Combining the studies showed an association between rare HRAS1 alleles and breast cancer (OR=2.03, 95% CI 1.72-2.40), with a PAR of 14%.…”
Section: Hras1mentioning
confidence: 99%
“…Of these, twenty were excluded [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Finally, a total of 13 studies were included in our meta-analysis [26][27][28][29][30][31][32][33][34][35][36][37][38], which included 1926 breast cancer cases and 2800 controls. Of those, two studies were population-based case-control studies, and eleven studies were hospitalbased case-control studies.…”
Section: Resultsmentioning
confidence: 99%
“…Although many studies have showed that rare HRAS1 alleles may be associated with breast cancer risk [26][27][28][29][30][31][32][33][34][35][36][37][38], this relationship remains controversial. A meta-analysis was conducted to investigate the potential association between rare HRAS1 alleles and breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%